2022
DOI: 10.1002/jcu.23265
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal syndrome: Pathophysiology as a key to the therapeutic approach in an under‐diagnosed disease

Abstract: Cardiorenal syndrome is a clinical condition that impacts both the heart and the kidneys. One organ's chronic or acute impairment can lead to the other's chronic or acute dysregulation. The cardiorenal syndrome has been grouped into five subcategories that describe the etiology, pathophysiology, duration, and pattern of cardiac and renal dysfunction. This classification reflects the large spectrum of interrelated dysfunctions and underlines the bidirectional nature of heart‐kidney interactions. However, more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 96 publications
0
11
0
1
Order By: Relevance
“…LUS is an easy, feasible, and fast evaluation method that adds significant value to the base characteristics of patients with heart failure. 6 , 7 The correlation of LUS with eGFR and hemoglobin indicates the ability to select more fragile heart failure patients, like the cardiorenal syndrome phenotype 8 and iron-deficiency phenotype, 9 at higher risk of cardiovascular events. This is further proved by its correlation with 3-month new-onset or worsening dyspnea.…”
Section: Commentsmentioning
confidence: 99%
“…LUS is an easy, feasible, and fast evaluation method that adds significant value to the base characteristics of patients with heart failure. 6 , 7 The correlation of LUS with eGFR and hemoglobin indicates the ability to select more fragile heart failure patients, like the cardiorenal syndrome phenotype 8 and iron-deficiency phenotype, 9 at higher risk of cardiovascular events. This is further proved by its correlation with 3-month new-onset or worsening dyspnea.…”
Section: Commentsmentioning
confidence: 99%
“…Nonetheless, different studies have shown that the incidence of renal failure is independent of blood pressure levels, and it is comparable among HF patients with reduced or preserved left ventricular ejection fraction (LVEF) [ 1 ]. Thus, it is reasonable to think that independently of the hemodynamic alterations, different other mechanisms are potentially involved in the pathophysiology of CRS as suggested by several evidence [ 1 , 30 , 31 , 32 ]. These mechanisms may include endothelial dysfunction; imbalance between ROS production/nitric oxide (NO) bioavailability; persistent RAAS activation; chronic inflammation (with neutrophil migration, leukocyte trafficking, cytokine production, cell apoptosis, chemokine secretion and immunologic imbalance) and the involvement of small noncoding RNAs and epigenetics alterations [ 1 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Pathophysiology Of Cardiorenal Syndromementioning
confidence: 99%
“…In patients with ADHF, static increases in volume overload lead to elevated central venous pressure (CVP). Elevated CVP is directly related to renal dysfunctionalities ( Prastaro et al, 2022 ). Increased CVP leads to depressed renal venous pressure (RVP), creating a low flow state that reduces the blood flow gradient to kidneys and leading to renal hypoperfusion ( Bock and Gottlieb, 2010 ; Prastaro et al, 2022 ).…”
Section: Pathophysiology Of Acute Crsmentioning
confidence: 99%
“…Elevated CVP is directly related to renal dysfunctionalities ( Prastaro et al, 2022 ). Increased CVP leads to depressed renal venous pressure (RVP), creating a low flow state that reduces the blood flow gradient to kidneys and leading to renal hypoperfusion ( Bock and Gottlieb, 2010 ; Prastaro et al, 2022 ). In patients with reduced cardiac functionalities, the low-flow state occurs due to kidney artery under-filling, resulting in a reduced eGFR (glomerular filtration rate) and reduced renal functionalities, which are associated with higher mortality ( Damman et al, 2009 ; Fu et al, 2021 ).…”
Section: Pathophysiology Of Acute Crsmentioning
confidence: 99%